Synthesis and structural charaterization of the alloys (CuInTe2)1-x (Cu3-MT-Te4) x (MT: Nb, Ta with x = 1/10, 1/5, 1/3, 1/2 y 2/3) (Publicaciones en Ciencias y Tecnología, 2017)
In this work we reported the characterization of the (CuInTe2)1-x (Cu3-BV- Te4)x (BV: Nb, Ta y x = 1/10, 1/5, 1/3, 1/2 y 2/3, alloys system using the techniques Scanning Electron Microscope (SEM), X- Ray Diffraction (XRD) and Differential Thermal Analysis (DTA). Alloys system was prepared by fusion and annealing direct fulfilling the rule of Grimm-Sommerfeld. The work is based on the thermograms of the CuInTe2 and Cu3NbTe4 compounds that were previously measured and incorporated in the phase diagrams for the system (CuInTe2)1-x (Cu3-MT-Te4) at x = 0 and x = 1; with the intention of obtaining the best information of the phases from x = 0 to x = 1. In these phase diagrams of the alloy family, we obtained in the concentration ranges, the following phases: in 0 < x < 0,1, the phase type chalcopyrite, for 0 < x
Keywords: Semiconductors; alloys, X-ray; diffraction; differential thermal analysis; phase diagram